The Empirical Assessment of Vibration in HVAC Systems - Farhad Forouharmajd; Shiva Soury; Mehran Mokhtari; Zahra Mohammadii (علوم بهداشتی ایران, 2021)
Background and purpose: Vibration caused by ventilation systems in buildings is one of the harmful physical factors that can cause harm to residents. Therefore, measuring and controlling vibration is important. Materials and Methods:  In the first step of the study, the vibration accelerometer was placed on the base of a fan where the vibrations were sent toward the duct wall. A vibration assessment of the building was conducted in the other steps to compare with guidelines. In the next step, the isolation method was used to control vibration. By placing the isolator on the duct wall, the accelerometer was located on the body of the duct wall and the value of vibration was measured in a millimeter per second. All stages of the experiment were performed in the Faculty of Health of Isfahan University of Medical Sciences in 2018. Results: The maximum vibration velocity reduction in the building was related to the frequency of 68 Hz, which reached 33 mm/s after isolation. In addition, the fan vibration at 485 Hz was equal to 2.1 m /s, which decreased to 2 mm /s after isolation. Conclusions: Comparison of vibration after fan isolation with standard showed that this method has been effective in reducing the fan vibration resulting in the vibration to reach below the standard.